Money and income : an outline of monetary economics - Day, A. C. L.; Beza, Sterie T. (New York : Oxford University Press, 1960)
The book attempts to give a systematic presentation of present day monetary economics in a form suitable for an American audience. It placed particular emphasis on the problem of inflation; stabilization policies and the international finance.
"Based on Outline of monetary economics, by A.C.L. Day." It also includes index
usc 29/06/2017
Loans
Keywords: Money